Valid problems of legal meaning such category as “state regulation” in the view of the necessity to provide ecologically favounable regime of managing in agrarian sphere of the national economy - Бейкун, А. Л. (Theory and practice of jurisprudence, 2016)
This article deals with etimological meaning, substantial loading and legal positions of certain categories, among their number: “state regulation” and “state management” that provide valid administratively-legal, economic-legal and ecologically-legal norms, which regulate corresponding relations in agrarian sphere of Ukrainian economy.